The Students’ Interference in Multilingual Class at MAN Kota Palangka Raya - Altalarik, Agel; Ikrimah, Ikrimah; Afdalia, Tiara; Pratama, Yogi Atma; Asi, Natalina (Universitas Negeri Makassar, 2024)
Abstrak. The phenomenon of interference occurs in sociolinguistics when one language or dialect impacts another. This study was conducted with the objective to shed light on the specific types of phonological interference experienced by students in a multilingual class at MAN Kota Palangka Raya. Employing a descriptive qualitative research design, this investigation focused on the phonological aspects influenced by students' native languages—Banjarese and Dayakese. The research revealed that students exhibit tendencies of Sound Addition, Sound Omission, and Sound Replacement across both language groups as they navigate between their mother tongues and English. The findings stress the complexities involved in English language teaching in environments where students' linguistic backgrounds are diverse. Understanding the nature of phonological interference can equip educators with the necessary tools to develop pedagogical strategies that are attuned to the linguistic challenges faced by multilingual students. This, in turn, can aid in fostering a more effective and inclusive approach to language education that helps diminish language acquisition barriers attributed to the influence of the learners' first languages. Keywords: Interference, Multilingual, Sound Addition, Sound Omission, Sound Replacement.